RENEWAL OF ATTORNEY GENERAL REGULATION NUMBER 15 OF 2020 CONCERNING TERMINATION OF PROSECUTION BASED ON RESTORATIVE JUSTICE IN CORRUPTION CASES THAT PRIORITIZE SAVING STATE LOSSES - Dhita, Gigih Juang; Karo, Lidia Br.; Herlambang, Herlambang (Bengkoelen Justice : Jurnal Ilmu Hukum, 2024)
The current handling of corruption cases emphasizes punishing the perpetrators and recovering state financial losses caused by corruption. Since 2010, the Attorney General's Office has issued internal regulations for resolving corruption cases through a restorative justice approach. These internal regulations allow for the resolution of corruption cases in a non-punitive manner that prioritizes the saving of state losses. The problems were addressed: (1) what is the possibility of resolving corruption cases prioritizing saving state losses through the renewal of Attorney General Regulation Number 15 of 2020 concerning the Termination of Prosecution Based on Restorative Justice? (2) What is the influence and obstacle if Attorney General Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice is applied to Corruption Cases? The type of research used in this thesis was normative legal research. The research results show that: (1) Theoretically and juridically, the concept of restorative justice in corruption cases could be implemented to realize one of the objectives of punishment, which provided a deterrent effect and maximized the return/safety of state losses oriented toward the national economy and were in line with the ultimum remidium principle which could streamline the implementation of the principles of simple, fast and low-cost justice. (2) The factor that influenced and obstructed when Attorney General Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice was applied to Corruption Cases was that the process of termination of prosecution based on restorative justice in Attorney General Regulation No. 15 of 2020 did not specifically explain the termination of prosecution in corruption cases. Keywords: Law Reform, Corruption, Restorative Justice, State Losses